Division of labour and job specialization as catalysts for better job performance among the staff of a Nigerian university library (2013)
This study brought into fore some salient discoveries about the strength and weaknesses of division of labour and job specialization on the overall job performance of the staff of a Nigerian university library. A descriptive survey method was adopted to elicit information from the respondents. A questionnaire was designed with 30 structured questions including the demography of the respondents. Fifty (50) copies of questionnaires were distributed among the library staff of Federal University of Agriculture, Abeokuta and forty five (45) were returned. Forty two (42) out of these were found usable. This study finds that majority of respondents agree that job specialization makes their work easier and faster, enhances their job performance and they are fully satisfied with their present area of specialization, while a sizable number were dissatisfied because their training does not correspond with their present posting. The study also finds that library and information centres still cannot do without division of labour and job specialization even with the emergence of ICT infusion into library and information services provision. The respondents also preferred the present division of labour although a paltry number disagreed. Recommendations were made based on the findings of the study and conclusions drawn.